1992
DOI: 10.1007/bf01307583
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of metoclopramide and domperidone on esophageal peristalsis and esophageal acid clearance in reflux esophagitis

Abstract: The acute effects of oral metoclopramide (40 mg/day) and domperidone (80 mg/day) on esophageal motor activity and acid reflux were assessed in a randomized, double-blind, placebo-controlled study in 20 patients with erosive reflux esophagitis. Esophageal motor function was assessed by standard manometry with wet swallows, and reflux events were evaluated by ambulatory 24-hr pH-monitoring. Both drugs caused a significant (P less than 0.05) increase in lower esophageal sphincter pressure lasting at least 120 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 28 publications
1
28
0
6
Order By: Relevance
“…However, presence of IMD was not associated with significant alteration in treatment resulting in low clinical utility in our study group. This finding is consistent with earlier studies demonstrating no change in IMD after antireflux surgery [13], oral prokinetic therapy [14,15] or acidsuppressive medications [16,17]. Esophageal manometry is also advised routinely in patients being considered for anti-reflux surgery.…”
Section: Discussionsupporting
confidence: 88%
“…However, presence of IMD was not associated with significant alteration in treatment resulting in low clinical utility in our study group. This finding is consistent with earlier studies demonstrating no change in IMD after antireflux surgery [13], oral prokinetic therapy [14,15] or acidsuppressive medications [16,17]. Esophageal manometry is also advised routinely in patients being considered for anti-reflux surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that neither metoclopramide nor domperidone effectively stimulate esophageal body motility, although both agents increase LES resting pressure in healthy volunteers [21,22] . Although several studies initially reported that cisapride increased both LES pressure and the amplitude of contractions in the distal esophagus [23][24][25] , a number of other studies failed to confi rm any direct prokinetic effects of cisapride on the esophagus [20,26] .…”
Section: Non-achalasia Esophageal Motility Disordersmentioning
confidence: 99%
“…It seems, therefore, that the reported effectiveness of domperidone stems from the acceleration of gastric emptying rather than from its effect on esophageal motor function. 10,11,18 We used the new technique of HRM, allowing a better evaluation of esophageal motility and a more detailed investigation of the effect of drugs on esophageal motor function. 8,19 Our data show that esophageal Esophageal peristalsis and LES function are under control of the autonomic and enteric nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…Domperidone, a peripheral dopamine antagonist, is currently the most common prokinetic agent used in clinical practice in patients with SSc, although data on its effect on esophageal motility are conflicting. 10,11 Recent data suggest that buspirone, an orally available 5-HT 1 A receptor agonist, enhances esophageal peristalsis and LES function in healthy subjects. 13,14 Given the paucity of drugs that are able to enhance esophageal motor function in SSc, 15 we conducted an open-label, pilot study in 20 symptomatic SSc patients aiming to test the hypothesis that buspirone could exert a beneficial acute effect on esophageal motor dysfunction and LES pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation